An ontology for human-machine computation workflow specification - Luz, Nuno (2014)
Lately, a focus has been given to the re-usability of workflow defini-tions and to flexible and re-usable workflow components, culminating with ap-proaches that harness the benefits of the enriched semantics provided by ontol-ogies. Following this trend and the needs of multiple application domains, such as micro-task crowdsourcing and ambient assisted living, of incorporating co-operation between the efforts of human and machine entities, this paper propos-es an ontology and process for the definition, instantiation and execution of se-mantically enriched workflows.